Efektivitas Penggunaan Media Sosial Instagram dalam Meningkatkan Citra Kepolisian Polsek Delitua - Maulana Akbar Ginting; Yose Rizal Saragih; Laila Rohani (Communication & Social Media, 2021)
This article discusses the effectiveness of the use of Instagram social media in improving the image of the Delitua Police Police. In the current era of globalization, information and communication technology is developing so fast. Social media seems to be a mediator that can encourage the dissemination of information. One of the social media that is widely used in conveying information and communication is Instagram. This article uses qualitative research methods. The data in this study were obtained from the results of interviews with Delitua police personnel. The results of the study show that Instagram is a very effective social media in building the image of the Delitua Police Sector Police. Not only that, Instagram social media also makes it easier for people to communicate with the Delitua Police and make complaints.